Le mal énucléé : Georges Bataille et consortes - Swoboda, Tomasz (Romanica Silesiana)
The identification of evil with the ocularcentrism of western civilization constitutes one of the leitmotifs of French theory. In words of Martin Jay, it results in a “denigration of vision” in the twentieth-century thought. This paper analyses only one form of this campaign against the visual evil, one related to the motif of the gouged, or enucleated, eye, as it appears in some literary and visual works of the authors from outside the surrealist circle. The study contains reflections on Georges Bataille’s early writings, as well as on works by Alberto Giacometti and Man Ray, and on one passage from Michel Leiris’s Manhood. Key words: Eye, Georges Bataille, Michel Leiris, Alberto Giacometti, Man Ray.